Characterization of collagen fibrils after equine suspensory ligament injury: An ultrastructural and biochemical approach. Issue 1 (April 2015) - Shikh Alsook, M.K.; Gabriel, A.; Salouci, M.; Piret, J.; Alzamel, N.; Moula, N.; Denoix, J.-M.; Antoine, N.; Baise, E.
Highlights A biochemical and structural study of the equine SL after injury is reported. Purified fibrils of types I, III, and V collagens were analysed. Significant changes in types I, III and V collagen in damaged SL are recorded. These changes are highlighted for several months in injured tissue. Quantitative data and structural observations are highly related.